Avaliação da viabilidade econômica da recria de bovinos de corte em sistema de pastagem irrigada - Umezaki, Adriano Moreira (2018)
In Brazil, the main source of beef production is pasture, which in turn requires the use of techniques that allow the improvement and potentialization of its use to become more effective, thus, the use of irrigation of pastures enters as an important tool to be used during the seasonality of production. The analysis of the activity related to its cost of production and its technical and economic indicators is a way of defining the decision making in a production system. The objective of this work is to analyze the economical viability of the pasture irrigation system with steers in recreat. The data collection for the calculations and analyzes of this work was carried out from an experiment that was conducted in the field from June 2016 to April 2018, in the county of Dois Vizinhos, at the Teaching and Research Unit (UNEPE) of Bovinocultura de Corte, from the Universidade Tecnológica Federal do Paraná, where performance indicators were processed in a Microsoft Excel spreadsheet. The daily live weight gain had an average of two years of GPD 0.84 kg / day. The internal rate of return on invested capital per hectare was 21%. The equilibrium point in physical units was 29.19 @ / ha. The use of irrigation increased the productive indices of the system and proved to be economically viable. This ensures a stability in the final production, making the rainfall factor not be limiting in the system.